2004
DOI: 10.3748/wjg.v10.i11.1589
|View full text |Cite
|
Sign up to set email alerts
|

Community-based survey of HCV and HIV coinfection in injection drug abusers in Sichuan Province of China

Abstract: Shared needles and syringes in the past 3 mo and syphilis infection were significantly associated with HCV infection. Further sero-epidemiological prospective cohort studies should be conducted to clarify the impact of syphilis and high risk sexual behaviors on HCV transmission through unprotected sexual intercourse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
3
21
1
Order By: Relevance
“…High HCV prevalence and co-infection rate with HIV were observed previously among IDUs in some areas of China [4,12,16,18,20,28,30]. Here, we found that HCV prevalence were 81.6 and 69.9% among IDUs and all drug users in Zhenjiang, Jiangsu (Table 1), respectively, slightly lower than 88.5 and 75.5% in other neighbor cities of Jiangsu, respectively [5].…”
Section: Discussioncontrasting
confidence: 60%
“…High HCV prevalence and co-infection rate with HIV were observed previously among IDUs in some areas of China [4,12,16,18,20,28,30]. Here, we found that HCV prevalence were 81.6 and 69.9% among IDUs and all drug users in Zhenjiang, Jiangsu (Table 1), respectively, slightly lower than 88.5 and 75.5% in other neighbor cities of Jiangsu, respectively [5].…”
Section: Discussioncontrasting
confidence: 60%
“…Injection drug users (IDUs) are at increased risk for HBV, HCV and HIV infections through the mode of sharing injection equipment [27]. Studies have shown that coinfection with HCV can reach above 90 % in HIVinfected subjects [17,33,38], while in high-HBV-prevalence countries, the prevalence of HBV surface antigen (HBsAg) among IDUs has been shown to be 10-20 % [14]. East Asia is believed to have the largest populations of IDUs with viral hepatitis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous exposures-including reuse of needles and syringes, injection drug use, and transfusion of unscreened blood products-are well-established risk factors. Two Chinese studies published in 2004 showed that 170% of injection drug users (IDUs) in Sichuan and Guangxi Provinces were seropositive for HCV antibodies [3,4], compared with 60% of IDUs in the United States [5]. In most industrialized countries, the risk of acquiring HCV infection through blood transfusion is now significantly reduced, because transfused blood is screened and risk behaviors in donors are identified.…”
mentioning
confidence: 99%